Media Framing in The 2024 Presidential Election Contestation and Its Relevance to Critical, Tolerant, and Moderate Learning in Islamic Higher Education - Lukman Hakim; Aris Nurbawani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Media framing is a form of news framing. In Indonesia, there are many mass media, each of which has a different background. Media framing related to the 2024 presidential election contestation can be influenced by the background of the media. Learning related to media framing is important to teach critical, trustworthy, and moderate attitudes. The purpose of this research. First, to analyse media framing related to the 2024 presidential election. Second, to analyse media framing and its relevance to critical, trustworthy, and moderate education in Islamic universities. This research uses a qualitative descriptive approach. The results of this study are that the media have different tendencies in reporting the 2024 Presidential Election Contest and framing analysis can provide learning to students about Islamic values such as objective critical, trustworthy, and standing in the middle in the truth at Islamic Universities. This research is expected to illustrate the importance of upholding Islamic values in facing the challenges of digital disruption with all the issues in it. Abstrak Framing media merupakan bentuk pembingkaian berita. Di Indonesia terdapat banyak media massa yang masing masing memilkii latar belakang berbeda. Framing media terkait kontestasi Pilpres 2024 dapat dipengaruhi oleh latar belakang media tersebut. Pembelajaran terkait framing media penting dilakukan untuk mengajarkan sikap kritis, amanah, dan moderat. Tujuan penelitian ini. Pertama, menganalisis framing media terkait Pilpres 2024. Kedua, menganalisis framing media dan relevansinya dengan pendidikan kritis, amanah, dan moderat di perguruan tinggi keislaman. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Hasil penelitian ini yaitu media memilik kecenderungan yang berbeda dalam memberitakan Kontestasi Pilpres 2024 dan analisis framing dapat memberikan pembelajaran kepada mahasiswa tentang nilai nilai keislaman seperti kritis objektif, amanah, dan berdiri di tengah dalam kebenaran di Perguruan Tinggi Keislaman. Penelitian ini diharapkan memberi gambaran pentingnya menjunjung tinggi nilai keislaman dalam menghadapi tantangan disrupsi digital dengan semua dinamikanya. Keywords: Framing; Media; Presidential Election; Critical Discourse; College